Public Awareness of Intestine Protozoa Risk Factors in Koncang Village Pandeglang Banten and Its Review According to Islam - Muhammad Hafizh Al-Fatah Imanov; Ambar Hardjanti; Firman Arifandi (Junior Medical Journal, 2023)
Introduction: Intestinal protozoa are widely distributed throughout the world, especially in tropical countries with poor sanitation. WHO estimates that around 3.5 billion world population, especially children, are infected with various types of intestinal parasites, and as many as 450 million of them fall ill. Indonesia has a relatively high prevalence with incidence rates of intestinal protozoa reaching 10-18%. The purpose of this study was to determine public awareness of the risk factors for diseases caused by intestinal protozoa in the Pandeglang community in Koncang Village.Method: This research is descriptive quantitative with cross sectional approach. The population in this study were the people of Koncang Village, Pandeglang Regency, totaling 49 people. The type of data is primary data using a previously prepared questionnaire. The technique used in data analysis is the chi-square test.Result: The results showed that the level of public knowledge about intestinal protozoa disease was not good, the level of community attitude was good, the level of community behavior was good. Based on the results of statistical tests, there is a relationship between knowledge and behavior towards intestinal protozoa disease in the people of Koncang Village, Pandeglang Regency, with a p-value of 0.019 (p-value 0.05). There is no relationship between attitudes and behavior in the people of Koncang Village, Pandeglang Regency, with a p-value of 0.906 (p-value 0.05).Conclusion: There is a statistically significant relationship between knowledge and behavior towards intestinal protozoa disease. There was no statistically significant relationship between attitudes and behavior towards intestinal protozoa disease.